The Family Business And Inheritance Dispute : A Review Of Legal Solution In Kinship Corporations - Zaini Munawir; Azwir Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Family businesses play a significant role in the economy, especially in developing countries. However, the sustainability of these businesses is often disrupted by inheritance disputes that arise when the founder dies without a clear succession system. Such disputes not only affect business continuity, but also lead to disintegration in the kinship structure. This research aims to examine the legal solutions available in dealing with inheritance disputes in kinship-based family businesses (kinship corporation), as well as to offer relevant legal approaches to ensure the sustainability of family businesses. The research method used is normative juridical with statutory, conceptual, and case approaches. The data analysis technique is carried out qualitatively with prescriptive-analytical, to assess the effectiveness of legal norms in resolving internal conflicts of family businesses. The novelty of this research lies in the interdisciplinary approach that combines the perspectives of inheritance law, corporate law, and legal sociology to form a holistic dispute resolution framework in family corporations. The results show that the absence of a binding legal structure and formal succession mechanism is the main root of conflict. It is necessary to strengthen internal regulations (internal by-laws), family agreements, and create a more comprehensive legal framework to accommodate the problem of inheritance disputes in family businesses. The recommendation of this research is the establishment of a family governance framework in positive law that regulates succession and ownership portion, as well as strengthening the role of notaries in designing family agreements based on inheritance and corporate law.